The Difference Between Breastfeeding and Complementary food with Nutritional Status in Infants Aged 6-24 Months in the Working Area of the Pare Health Center : Perbedaan Antara Pemberian ASI dan MP-ASI dengan Status Gizi pada Bayi Umur 6-24 Bulan - Fitriyadi, Junianto; Yunita, Astri; Alfonsa, Alfonsa (Poltekkes Kemenkes Palu, 2023)
Background: The problem of malnutrition in toddlers is the impact of low exclusive breastfeeding for up to 6 months and improper breastfeeding because it is given too early or too late, the amount is not enough to meet the needs of growth and development of babies at each age stage. Objective: to determine the difference between breastfeeding and MP-ASI with nutritional status in infants aged 6-24 months. Method: This study used a cross-sectional design. The study sample was mothers who had babies aged 6-24 months as many as 30 respondents with 2 groups of breastfeeding and MP-ASI (15 respondents per group) using quota sampling. The research was placed in the working area of the Pare Health Center for 2 weeks with questionnaire instruments according to the experience of breastfeeding and MP-ASI, as well as Z score measurement. Analysis of paired sample t-test. Results: The results of this study showed that most of the 15 respondents breastfeeding had less nutritional status as many as 9 respondents (60%), while of the 15 respondents of MP-ASI most had good nutritional status as many as 10 respondents (66.7%). Conclusion: Families must be more careful in understanding the nutritional needs of infants with a combination of nutritional content needed by the body in accordance with the stage of development and nutritional needs in infants aged 6-24 months.